2023
DOI: 10.31234/osf.io/m8fhk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

●Repeat after me? Both Children with and without Autism Commonly Align Their Language with That of Their Caregivers

Abstract: Introduction: The role of linguistic repetition in child language is complicated. Echolalia, the persistent repetition of one’s interlocutor’s utterances, has long been associated with Autism Spectrum Disorder (ASD). The literature on echolalia suggests that children with ASD often re-use fragments of language without any communicative or language-learning purpose. At the same time, research on linguistic repetition in typically developing (TD) children and adults increasingly demonstrates that linguistic repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…Interestingly, we see similar effects for entrainment rate and level (both higher in Danish than Norwegian), where previous studies show important differences in their behavior related to the context (Dideriksen et al, 2023) or the development of linguistic and conversational skills (Fusaroli et al, 2023a(Fusaroli et al, , 2023bMisiek, Favre, & Fourtassi, 2020). However, as in previous literature, rate presents bigger variations related to language and context than level does.…”
Section: Linguistic Entrainmentsupporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, we see similar effects for entrainment rate and level (both higher in Danish than Norwegian), where previous studies show important differences in their behavior related to the context (Dideriksen et al, 2023) or the development of linguistic and conversational skills (Fusaroli et al, 2023a(Fusaroli et al, , 2023bMisiek, Favre, & Fourtassi, 2020). However, as in previous literature, rate presents bigger variations related to language and context than level does.…”
Section: Linguistic Entrainmentsupporting
confidence: 86%
“…Fully overlapping speech between interlocutors occurred occasionally (e.g., during some backchannels) and was interleaved at the first pause longer than 1 s in the speaker holding the floor. The impact of different definitions of conversational turns on, for example, measures of alignment has been assessed in (Fusaroli, Weed, Rocca, Fein, & Naigles, 2023a, 2023b and showed the robustness of the findings to changes in definition. Relying on videos and transcripts, backchannels and the three kinds of repairs were manually coded.…”
Section: Corpora and Participantsmentioning
confidence: 99%
“…In this study, we extended previous findings to a semi‐structured naturalistic conversational paradigm encompassing contexts that would more closely represent children's daily conversations. Previous literature has demonstrated that younger children use lexical alignment as a language learning strategy (e.g., Fusaroli et al., 2023b; Rydland & Aukrust, 2005; Strapp & Federico, 2000). In contrast, adults, who already have fully developed linguistic systems, use alignment to facilitate social communication (Huiyang & Min, 2022; Ireland et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This paper specifically explores lexical alignment, where conversational partners adapt their language and reuse one another's words. The phenomenon of lexical alignment has been observed in adult–adult and adult–child conversations (e.g., Dideriksen et al., 2023; Duran, Paxton, & Fusaroli, 2019; Fusaroli, Weed, Rocca, Fein, & Naigles, 2023b). Both theoretical models and empirical evidence suggest that lexical alignment is crucial for supporting communication success by facilitating cognitive, emotional, and pragmatic functions (e.g., Dideriksen et al., 2023; Nenkova, Gravano, & Hirschberg, 2008; Rasenberg et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation